Psycholinguistic Analysis of Language Disorders (Speech Delay) in Early Childhood and Treatment Efforts - Aldi Saprianta Sitepu; Vivi Wulandari; Nur Cristina; Rike Andini; Jonathan Nainggolan; Sri Kurnia Hastuti Sebayang (Jurnal Pendidikan Indonesia, 2026)
This study aims to analyze language disorders (speech delay) in early childhood from a psycholinguistic perspective and identify various treatment efforts. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation of early childhood children, parents, and teachers. The results of the study indicate that speech delay in early childhood is influenced by various factors, including a lack of language stimulation in the family, excessive use of gadgets, minimal verbal interaction between children and their surroundings, and children's emotional factors. In psycholinguistic studies, speech delay occurs due to obstacles in the process of language acquisition, especially in the aspects of phonology and semantics. These obstacles cause children to experience difficulty in pronouncing words, understanding the meaning of language, and communicating verbally. Children with speech delay also tend to be more passive in social interactions and lack confidence when communicating with others. Treatment efforts include providing regular language stimulation through active communication, speech therapy, educational play activities, and collaboration between parents, teachers, and professionals. The results of the study indicate that consistent treatment can help improve children's speaking and social interaction skills gradually. Thus, communicative and stimulating environmental support is an important factor in helping the language development of early childhood children who experience speech delay.